Encorafenib plus cetuximab for the treatment of BRAF-V600E-mutated metastatic colorectal cancer. (July 2022) - Ros, Javier; Saoudi, Nadia; Baraibar, Iosune; Salva, Francesc; Tabernero, Josep; Elez, Elena
B-type RAF ( BRAF ) -V600E mutations in metastatic colorectal cancer (mCRC) have been described in up to 12% of the patients. This mutation confers a bad prognostic and poor response with standard chemotherapy. Unlike the scenario for BRAF mutant melanoma, successful BRAF blockade in mCRC has emerged as a complex path, primarily due to the complex underlying biology of mCRC. The BEACON trial has reshaped the therapeutic landscape of BRAF mCRC demonstrating the benefit of the BRAF inhibitor encorafenib in combination with the anti-epidermal growth factor receptor cetuximab. This paper aims to review the main features of BRAF mCRC as well as to review the development of targeted therapy and biomarkers in this specific population. Finally, a deep insight into the underlying biology and molecular classification of BRAF-V600E mCRC has also been performed. The words 'BRAF-V600E mutation', 'colorectal cancer', 'BRAF inhibitors', 'consensus molecular subtypes', 'encorafenib', and 'cetuximab' were used to identify the clinical trials from phase I to phase III related to the development of BRAF inhibitors in this population. A deep search among international meetings (American Society of Clinical Oncology and European Society of Medical Oncology) has been performed to incorporate the last trials presented. BRAF-V600E mCRC is a challenging disease, mostly because of its molecular biology. The BEACON trial has been the most important therapeutic change in the last decade. Nevertheless, new information regarding biomarkers or novel combinations including BRAF inhibitors plus immune checkpoint inhibitors are also promising.